Gender-associated role in patients with schizophrenia. Is there a connection with the resistance? - Panov, Georgi (Frontiers in Psychiatry, 2022)
Schizophrenia is a serious mental illness, the treatment of which represents a serious challenge. A number of factors associated with treatment resistance have been identified. We set ourselves the goal of establishing the relationship of identification with a certain gender role and the lack of response to therapy, as well as with some features in the course of schizophrenia, such as the age of onset and its duration.